Innowacje i strategie przedsiębiorstw : analiza sytuacji MŚP w regionie łódzkim - Jewtuchowicz, Aleksandra (Innovations and Strategies of Enterprises : Analysis of the Situation of the SME's in the Region of Łódź, 2005)
The permanent implementation of innovations is a condition for the competitiveness of an enterprise. Nowadays innovation is not an exception but a rule in most of the organizations. The multilateral processes, implemented by the enterprises, foster the creative activities and are characterized by their permanence which enables the collective learning, providing many possibilities that the individual learning does not provide. The implemented innovation helps to differentiate firm's products and brings to life imitative behaviours of other enterprises, leading to general productivity growth and spreading the new technologies in the whole branch. This permanent process of innovation mobilizes entrepreneurs and can motivate them to look for external support which, in fact, can lead to the development of the partnership relations and creating the innovative milieu. The innovative milieu, in turn, fosters and supports the processes of innovation. Since innovation derives from permanent adaptation of the firm to the environment, it demands taking into consideration the dynamics and the time. It is a global process, that is outside-open and leads to creating new resources and competences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 75-85